Quality of life in patients of erectile dysfunction: a cross sectional study in tertiary care settings - Langer, Raja; Gupta, Rushali; Thaker, Kailash Singh; Kumari, Rashmi; Gupta, Rajiv K.; Langer, Bhavna (International Surgery Journal, 2019)
Background: Normal sexual desire coupled with physical inability to act is a major source of mental stress in interpersonal relationships which subsequently affects the quality of life of patients. Methods: The present cross sectional study was conducted among patients of erectile dysfunction visiting the Urology OPD of tertiary care hospital. Study instruments used were international index of erectile function (IIEF) to assess sexual functions and version of the WHO QOL scale (WHOQOL-BREF) to assess quality of life. Results: 168 patients were interviewed and 62.5% of them were less than 45 years of age. Age, income and presence of co-morbidity were found to be statistically significantly associated with ED (p<0.05). Overall QOL scores were lower in severe grades of ED as compared to milder grades and this difference was found to be statistically significant (p<0.05). Conclusions: Erectile dysfunction has a significant impact on the quality of life of the patients which reemphasizes the need to diagnose and manage ED at the earliest.